Viruses of herbaceous legumes in the moist savannah of West Africa - Hughes, J.D.A.; Tarawali, Shirley A. (1999)
Virus diseases of herbaceous legumes have been relatively little studied even though the legumes play an important role in the maintenance of soil fertility and pest/disease management as well as providing fodder in sub-Saharan Africa. Leaf samples exhibiting virus-like symptoms from nine herbaceous legume genera (Aeschynomene, Arachis, Calopogonium, Centrosema, Chamaecrista, Cratylia, Dicolea, Stylosanthes and Zornia) were tested for 12 viruses reported to occur in herbaceous legumes. Although six viruses (blackeye cowpea mosaic, peanut mottle, bean common mosaic and bean yellow mosaic potyviruses, cucumber mosaic cucumovirus and tobacco mosaic tobamovirus) were detected, some symptomatic samples tested negative. These were examined by electron microscopy and virus-like particles were observed.